Effects of wheat gluten protein on the properties of starch based sustainable wood polymer nanocomposites. (March 2018) - Baishya, Prasanta; Nath, Deepankar; Begum, Pakiza; Deka, Ramesh C.; Maji, Tarun K.
Graphical abstract: Highlights: Complete renewable resources like polymer, cross-linker, reaction media and reinforcing agent has been used to prepare the nanocomposites. Water has been used as the reaction media in the entire process. The density functional theory (DFT) calculations supported the interactions among different components during the formation of wood starch gluten nanocomposites (WSGNC). Thermal resistance, water resistance and mechanical properties of the composites were improved significantly with the addition of 3 phr nanoTiO2 . Abstract: Wood polymer nanocomposites (WPNC) having attractive mechanical and water resistance properties were prepared through a completely green route using a mixture of wheat gluten protein and starch. Starch was blended with wheat gluten protein at different ratios (70/30 and 50/50) and then grafted with methylmethacrylate (MMA). The effect of wheat gluten protein on various properties of the wood composites was investigated. Citric acid was employed to cross-link the wood flour with methylmethacrylate grafted starch-gluten (MMA- g -SG). The most advantageous part of the reaction was the use of water as the reaction media in the entire process to prepare the green composites. To improve the further properties of the composites, different percentage of N-cetyl-N, N, N-trimethyl ammonium bromide (CTAB) modified TiO2 nanoparticles were incorporated in the composite system and their effects were studied. The interaction among MMA- g -SG, cross-linker, soft wood flour and nanofiller were investigated by FTIR study. The probable interactions among MMA- g -SG, soft wood, modified TiO2 and citric acid in the formation of wood starch gluten nanocomposites (WSGNC) were established. The density functional theory (DFT) calculations were also used to study the interactions of the nanocomposite. The morphology of the wood starch gluten nanocomposites (WSGNC) was examined by SEM and TEM study. Composite prepared from 50/50 ratio of starch and gluten along with 3 phr TiO2 exhibited excellent thermal resistance, water resistance and mechanical properties.